PENGARUH PEMBERIAN REWARD TERHADAP KINERJA PADA KARYAWAN PT. MEGA AUTO CENTRAL FINANCE CABANG KENDARI - Thomas, Alfin (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
This study aims to examine and explain the effect of giving rewards on the performance of employees of PT. Mega Auto Central Finance. The object of this research is limited to employees of PT. Mega Auto Central Finance Kendari Branch. Determination of the sample using the census method. The sample in this study were 38 employees. Data collection was done by using a questionnaire.The results of this study indicate that the reward variable has a positive and significant effect on employee performance.Employee performance can be improved if an employee gets a reward from the company.Rewards can affect employee performance, because rewards will satisfy a number of needs that employees are trying to fulfill through their choices of work-related behavior so that when employee satisfaction is met, their concern for work will increase.